Beyond physical recovery: psychological readiness, well-being, and rehabilitation adherence following sports injuries in volleyball athletes - Rudyanto Rudyanto; Heru Syarli Lesmana; Juanda Putra (Indonesian Institute For Counseling, Education and Therapy, 2025)
Sports injuries are a frequent accompaniment to competitive volleyball; however, the mental consequences of these injuries are not as well examined as the biomechanical and epidemiological aspects. Previous research has mostly focused on the types of injuries and the results of physical rehabilitation, but the psychological recovery part is still scattered and lacks a comprehensive volleyball-specific review. Therefore, the current systematic review of the literature intended to compile evidence regarding psychological readiness to return to sport, emotional well-being, and adherence to rehabilitation after sports injuries among volleyball players. According to the PRISMA 2020 guidelines, a systematic search in the Scopus database was carried out, resulting in 856 records from 2020 to 2025. Eight studies, which after screening and evaluation for eligibility matched the inclusion criteria, were included in the thematic synthesis. Three interlinked aspects of psychological recovery were revealed. To begin with, the first aspect is the psychological readiness to return to sport (RTS) that showed a negative correlation with the presence of residual pain; and was also affected by the fear of movement/(re)injury i.e. kinesiophobia and self-concept as an athlete i.e. athletic identity. Besides, mood disturbances, increased arousal in competitive situations (competitive anxiety), changes in sleep patterns, impaired quality of life, and psychosocial dysfunctioning were among the negative effects of injury in general, with the most noticeable changes coming from season-ending injuries. The third finding, rehabilitation adherence was related to pain, social support, coping capacity, and self-efficacy. These results reinforce the biopsychosocial model of injury recovery and stress the necessity of implementing psychological screening and providing psychological support in the framework of rehabilitation programmes. The next research should focus on prospective studies, equal gender representation, and the use of standardised psychological assessment over the course of the volleyball injury continuum.